SAR-driven flood inventory and multi-factor ensemble susceptibility modelling using machine learning frameworks - Halder, Krishnagopal; Ghosh, Anitabha; Srivastava, Amit Kumar; Pal, Subodh Chandra; Chatterjee, Uday; Bisai, Dipak; Ewert, Frank; Gaiser, Thomas; Islam, Abu Reza Md. Towfiqul; Alam, Edris; Islam, Md Kamrul (Geomatics, natural hazards and risk, 2024)
Climate change has substantially increased both the occurrence and intensity of flood events, particularly in the Indian subcontinent, exacerbating threats to human populations and economic infrastructure. The present research employed novel ML models-LR, SVM, RF, XGBoost, DNN, and Stacking Ensemble-developed in the Python environment and leveraged 18 flood-influencing factors to delineate flood-prone areas with precision. A comprehensive flood inventory, obtained from Sentinel-1 Synthetic Aperture Radar (SAR) data using the Google Earth Engine (GEE) platform, provided empirical data for entire model training and validation. Model performance was assessed using precision, recall, F1-score, accuracy, and ROC-AUC metrics. The results highlighted Stacking Ensemble's superior predictive ability (0.965), followed closely by, XGBoost (0.934), DNN (0.929), RF (0.925), LR (0.921), and SVM (0.920) respectively, establishing the feasibility of ML applications in disaster management. The maps depicting susceptibility to flooding generated by the current research provide actionable insights for decision-makers, city planners, and authorities responsible for disaster management, guiding infrastructural and community resilience enhancements against flood risks.